Globalization and challenges to building peace - Swain, Ashok; Amer, Ramses; Öjendal, Joakim (Anthem studies in development and globalization., 2008)
This fascinating collected volume explores the relationship between world conflict, political unrest and the driving forces of Capitalism and Globalization.